Estudo da dinâmica dos sedimentos em suspensão do estuário do rio Araranguá (SC): possíveis efeitos da drenagem ácida da atividade de mineração de carvão - Couceiro, Mariana Afonso Abade (2010)
The Araranguá river estuary rises from the inflow of two main tributaries, the rivers Itoupava and Mãe Luzia. The former drains mainly agriculture and cattle raising areas, meanwhile the latter drains also coal mining areas, which produces acid drainage (pH < 4). One of environmental impacts of the latter is the acid drainage, when the streams pH can be decreased below 4. The low water pH enhance the suspended sediment flocculation, and the Mãe Luzia’s water are depleted of suspended sediments, meanwhile the contrary is observed for the Itoupavas river. When the waters from both rivers mix, the Itoupavas’ suspended sediment flocculates, inducing rapid settling along the estuary. The objective of the present study is to assess flocculation potential from the Mãe Luzia’s water during the mixing with the Itoupavas’ water, and comparatively with seawater. An annular flume was setup to simulated continuous flow, within were mixed the rivers waters, assessing the pH effects and salinity, separately and together. During every experiment the flow velocity was controlled to decelerated and accelerated at regular time intervals. The concentration of suspended sediments was continuously monitored with turbidity sensors. At every velocity change, water samples from the flume were taken for the assessing of floc settling velocity and shape in a settling chamber. The main findings are that the formation of macro-flocs and its settling take place mainly when the flow velocity is below than 15 cms-1, and, inversely, when the velocity is higher than 15 cms-1 the flocs are ressuspended and destroyed. The contribution of the Mãe Luzia water, even in small proportion, has the same flocculant effect than the mixing with salinity of one.